Association of iron rim lesions with brain and cervical cord volume in relapsing multiple sclerosis - Weber, Claudia Ellen; Krämer, Julia; Wittayer, Matthias Sebastian; Gregori, Johannes; Randoll, Sigurd; Weiler, Florian; Heldmann, Stefan; Roßmanith, Christina; Platten, Michael; Gass, Achim; Eisele, Philipp (European radiology, 2022)
In multiple sclerosis (MS), iron rim lesions (IRLs) are indicators of chronic low-grade inflammation and ongoing tissue destruction. The aim of this study was to assess the relationship of IRLs with clinical measures and magnetic resonance imaging (MRI) markers, in particular brain and cervical cord volume.